Strengthening the Role of Bhabinkamtibmas in Early Handling Efforts for Serious Criminal Acts in Rural Areas - Aji, Teguh Ari; Joko Setiono; Gani, Yopik (Jurnal Greenation Sosial dan Politik, 2025)
Serious crimes such as drug trafficking, premeditated murder, and acts of terrorism are now not only concentrated in urban areas but have also begun to spread to villages. This condition requires a more adaptive and preventive approach to handling them. This study aims to analyze the role of Bhabinkamtibmas in the early handling of serious crimes in rural areas through the perspective of positive Indonesian law. The research method used is normative juridical with a conceptual and legislative approach. Bhabinkamtibmas as an integral part of the structure of the Republic of Indonesia National Police has a clear legal basis, including Law Number 2 of 2002, Perpolri Number 1 of 2021 concerning Community Policing, and Perkapolri Number 7 of 2021 concerning Bhabinkamtibmas. Their roles include early detection functions, legal education, and mapping potential security disturbances. The results of the study show that implementation constraints include limited personnel and budget, low training on serious crimes, and minimal legal awareness among rural communities. On the other hand, collaboration between Bhabinkamtibmas and village officials, community leaders, and local institutions can increase the effectiveness of prevention. This study recommends reformulating the authority and increasing the structural capacity of Bhabinkamtibmas to deal with the escalation of serious crimes more responsively and comprehensively. By optimizing the preventive role of Bhabinkamtibmas, the prevention of serious crimes can be carried out in a more humane and community-based manner.